Fruit morphology of Durio zibethinus L. in Jelebu, Negeri Sembilan, Malaysia - Kamaruddin, Shamin Shazwan; Razali, N.I.A; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Go, Rusea (Argicultural Research, 2021)
Background: Jelebu is one of Negeri Sembilan districts of Malaysia, famous for its wide variety of D. zibethinus. It is also recognized as the top hotspot area for consumers looking for genuine Durian Kampung. This study aimed at discovering and recording significant morphological data in identification and classification of D. zibethinus fruit in Jelebu. Methods: Fifty-three accessions of durian were observed from January 2020 to September 2020 in accordance with Malaysia’s Department of Agriculture guidelines. Result: Forty-one parameters were compiled and divided into two primary morphological data sets: external and internal structures. Size, shape, color and aril characteristics of fruits were several engrossing parameters for identifying and classifying D. zibethinus varieties. Fruit weight varies between 665 g and 2.7 kg, depending on size. The results also revealed six different variants in the fruit shape and color. Aril characteristics included a variety of aril color and thickness ranging from 0.23 cm to 1.17 cm. Therefore, this research revealed that external and internal morphological data from durian fruits were valuable for recognizing and categorizing D. zibethinus Jelebu variants.